Antisperm antibodies as a factor of male infertility. Relevance, modern methods of diagnosis and treatment - O. A. Nikiforov; N. V. Avramenko; V. V. Mikhailov (Zaporozhye State Medical University, 2017)
According to WHO statistics 40 % of childless marriage is due to factors of male infertility. One of them is the presence of antisperm antibodies in the male organism, which may be in blood serum, on the surface of spermatozoids and seminal plasma. Aim. Оn the grounds of specialized literature analysis, to show the relevance of this problem in Reproductive Medicine, to descript Basic methods of Modern treatment and diagnosis of this pathology in the body of infertile males. The most common methods of antisperm antibodies identifying are: MAR-test sample Shuvarskiy-Sims-Hyuner, Kurtsrok-Miller test, the method of latex agglutination, solid-phase immunoenzymatic blood test. Indications for antisperm antibodies determining are: modified indices, deviations in post-coital test, a negative test of sperm and cervical mucus interaction in vitro, unexplained infertility in the married couples, failure or low indices during IVF (in vitro fertilization) and of course, the exclusion of other causes of infertility. When antisperm antibodies are detected, the strategy of treatment may be destined to reduction of their titer for further pregnancy. Such types of therapy can be used: contraceptive (long-term use contraception barrier to reduce antisperm antibodies titer in women), plasmapheresis, artificial insemination with pretreated from antisperm antibodies husband's sperm, methods of assisted reproductive technologies. Conclusoins. The formation of antisperm antibodies leads to infertility of immunological genesis (in 20 % of couples with unexplained infertility). To confirm their presence in the male body it is necessary to perform the MAR-test, Shuvarsky test, other tests and, of course, the exclusion of other causes of infertility. Men of reproductive age with an immunological factor of infertility provides for a comprehensive treatment, including elimination of all possible causative and contributing factors of infertility (infection of the male reproductive system, varicocele etc.), decreased production and removal of spermatozoa-associated antisperm antibodies and assisted reproductive technologies - intrauterine insemination and in vitro fertilization.